Treatment options for patients with relapsing and refractory peripheral T-cell lymphoma. (October 2014) - Reimer, Peter
SUMMARY : Peripheral T-cell lymphomas are rare malignancies that with the exception of ALK -expressing anaplastic large cell lymphoma show a poor outcome after conventional (anthracycline-based) chemotherapy. The median overall survival ranges between approximately 9–42 months. Most patients are refractory or relapsing, and need salvage treatment. Several strategies have been investigated for this setting, but data are sparse. Autologous and allogeneic stem cell transplantation can induce long-term remissions and cure in a subset of chemosensitive patients. In addition, novel agents are available and under investigation to improve the outcome in this challenging group of diseases.